A diffuse interface lattice Boltzmann model for thermocapillary flows with large density ratio and thermophysical parameters contrasts. (August 2019) - Hu, Yang; Li, Decai; Niu, Xiaodong; Shu, Shi
Highlights: A diffuse interface lattice Boltzmann model for thermocapillary flows is proposed. This model can simulate the thermocapillary flows with density ratio up to 1000. Thermophysical parameters of two fluids are allowed to be different. An unsteady solution for thermocapillary convection in two layer fluids is derived. Abstract: A diffuse interface lattice Boltzmann model for thermocapillary flows with large density ratio and thermophysical parameters contrasts is developed in this paper. In this model, three distribution functions are used to describe the evolution of phase field, velocity field and temperature field. The conservative Allen-Cahn-based lattce Boltzmann equation which has good numerical stability in simulating multiphase flows at high density ratio is employed to capture the phase interface. The velocity-based lattice Boltzmann equation is utilized to capture the hydrodynamics with thermocapillary effect. In particular, a lattice Boltzmann scheme is proposed to solve the temperature field equation based on the diffuse interface concept, in which the source term is computed locally. Unlike previous lattice Boltzmann model for thermocapillary flows, the thermophysical parameters (heat capacitance and thermal conductivity) of two fluids are allowed to be different. The present model is validated by simulating several numerical examples. Numerical results indicate the reliability of proposed diffuse interface lattice Boltzmann model in simulating thermocapillary flows with large density ratio (up to 1000) and thermophysical parameters contrasts. Moreover, we also derive an unsteady solution for thermocapillary-driven flow in a heated microchannel with two superimposed planar fluids, which can be used to assess the numerical accuracy of numerical algorithm for thermocapillary flows.